Three new species of the spiral nematode genus helicotylenchus steiner, 1945 (nematoda: hoplolaimidae) from Vietnam - Chau, Nguyen Ngoc; Anh, Do Tuan (Academia Journal of Biology, 2019)
Investigations on entomopathogenic and plant parasitic nematodes in some natural forests in the Ngoc Linh mountain (Quang Nam province) and the Thuong Xuan forest (Thanh Hoa province) revealed three new species of plant parasitic nematodes belonging to the genus Helicotylenchus Steiner, 1945 (Nematoda: Hoplolaimidae). These new species were named Helicotylenchus castanus sp. n., Helicotylenchus madhucus sp. n. and Helicotylenchus digitus sp. n. with morphological characteristics described and illustrated. The new species Helicotylenchus castanus sp.n.  is characterized by the highly hemispherical shape of the lip region, extremely short and rounded tail without projection. The second new species Helicotylenchus madhucus sp. n. is characterized by high lip region with 4-5 annuli, hemispherical and not set off from body contour, stylet 31.3-35.9 (33.3 ± 1.3) µm long, tail with a short ventral projection and the presence of males in the population. The third new species, Helicotylenchus digitus sp.n. was recognized by broad rounded tail with strong annulated projection in the digital shape, and also the presence of males in population.